Upaya Meningkatkan Produktivitas Sapi Bali Melalui Pengendalian Penyakit Parasit di Sekitar Sentra Pembibitan Sapi Bali di Desa Sobangan - Apsasri, I. A. P.; Swacita, I.B.N.; Ardana, I. B.; Kencana, G.A.Y.; Suada, I K. (Buletin Udayana Mengabdi, 2016)
This dedication aims to improving the productivity of Bali cattle through the control of parasites diseases at around Bali cattle breeding center in the village Sobangan. This service activities preceded the survey in cattle around Bali cattle breeding center in the village Sobangan, regarding the data of infection and illness. The method is applied for the attainment of the objectives of this activity is the administration of worms drugs directly to the breeder in around the Bali cattle breeding centers in Sobangan and extension of the maintenance management of cattle to prevent infection by the parasite. Service activities in the form of health services in Bali cattle was held on June 27th, 2015 in the village Sobangan Mengwi Badung Bali. These activities responded very well by livestock farmers around the Bali cattle breeding center in the village Sobangan. Conclusions dedication to the community around the Bali cattle breeding center in the village Sobangan has succeeded well implemented. Suggestions that the provision of worms drug in cattle regularly given, so that cattle can continue to increase the productivity.
Keywords: breeding center, bali cattle, Sobangan village, parasite disease, worm drug.